Probabilistic structure of errors in forehand and backhand groundstrokes of advanced tennis players - Delgado-García, G.; Vanrenterghem, J.; Muñoz-Garcia, A.; Ruiz-Malagón, E. J.; Mañas-Bastidas, A.; Soto-Hermoso, V. M. (International Journal of Performance Analysis in Sport, 2019)
Accuracy and speed are related to performance in tennis. Most research has focused on speed and little is known about the probabilistic structure of error (i.e. accuracy). In the present study 31 advanced players performed a standardised test and accuracy was measured using video analysis. Parameters describing 95% confidence ellipses (CEs) of forehand and backhand were calculated to determine the probabilistic structure of errors. Results showed that for both groundstrokes the long axis of the CEs was oriented almost parallel to the sideline. Despite greater ball speed (~107.2 vs. ~97.3 m • s-1; p < 0.001), the forehand showed a smaller longitudinal distance to the target than the backhand (~123.3 vs. ~164.0 cm; p = 0.024) and a smaller CE area (~34.4 vs. ~40.3 m2; p = 0.045). This means that tennis shot placements fit a bivariate normal distribution (represented by an ellipse), similar to other throwing sports, with differences between the forehand and backhand. Further research will need to explore the underlying causes of these distributions, which in turn may open up opportunities for coaches to modify them in their players according to what is deemed most vital for improved performance.